Pulmonary tuberculosis in pauper patients : with suggestions for their cure and treatment - Spark, Henry Langlands. (The University of Edinburgh, 1903)
The following Thesis is based on eighty consecutive cases of Pulmonary Tuberculosis admitted to the Bradford Workhouse Hospital. 'It deals more particularly with.. the relation of other diseases to Pulmonary Tuberculosis and with the treatment adopted; with added. notes on Phthisical patients under the Poor Law.